The marketing of surplus rice of the province of Iloilo wholesaler shippers' level. - Taningco, Maria Teresa Villalobos (1986.)
This study, the Marketing of Surplus Rice of the Province of Iloilo: Wholesaler-shippers' Level, is a descriptive work aimed to: describe the factors affecting the pricing practices of wholesaler-shippers in surplus rice marketing, identify the existing marketing channels for surplus rice, identify the final destinations of the surplus rice, and determine the marketing margins of Iloilo City-based wholesaler-shippers., This study was based on the marketing activities of February 1989. Primary and secondary data were used. Primary data were gathered from twenty-one (21) wholesaler-shippers by means of a census. Qualitative information were presented using tables and graphs. All marketing channels used were commercial, not governmental. NFA was not included (although they played a big role in data gathering). NFA operates differently from commercial middlemen as to marketing. Rice variety was limited to the high-quality IR series, the "superwhite". Pricing practices depended on factors such as: the supply and demand for rice, the co-traders' prices, the marketing cost, the buying price (procurement cost) of rice, the credit terms, the wholesaler-shippers' relationships with other traders or "kinship".
Thesis (Undergraduate, Bachelor of Arts in Economics-Management) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Rice, Surplus -- Wholesaler -- Research